Sartre et Nizan, politique des mots - Reato, Elisa (Labyrinth, 2020)
Sartre and Nizan, politique of words The aim of this article is to discuss and compare the main points of Nizan’s and Sartre’s views of committed literature. Discarding the claim to be objective and neutral, Nizan states that to abstain is to make a choice. Therefore, he critiques the intellectuals to be guilty of an abdication of responsibility. In his writings (specially Antoine Bloyé [1933], The Trojan Horse [1935], The Conspiracy [1938]) Nizan posed some questions, which became crucial for the postwar debates on the engagement of the intellectual. These questions constitute a central aspect of Sartre’s writings after World War II, where Sartre criticizes writers who had not taken a stance against oppression and delineates the axes of a theory of committed literature. As a result of the comparative analysis between the two authors, it is shown that Sartre articulates an important point that Nizan have missed, namely that there is a praxis, which is specific to literature and that we should part from it in order to understand commitment. Thus, at the difference of Nizan, Sartre points out that the liberating dimension of literary criticism should not be too quickly confused with armed criticism.